2020
DOI: 10.1002/ase.1994
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Anatomy Students toward Commemorations for Body Donors: A Multicultural Perspective

Abstract: Many medical schools practice commemorative ceremonies to honor body donors. Attitudes of medical education stakeholders toward these ceremonies have not yet been fully investigated. The aim of this study was to explore anatomy students' attitudes toward commemorations at a multicultural institution which has not introduced these ceremonies yet. A survey was carried out on different groups of anatomy students that were exposed and not yet exposed to human remains. The survey was used to record basic demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 78 publications
(114 reference statements)
2
25
0
1
Order By: Relevance
“…A study by Pearson et al demonstrated that after frequent exposures to cadavers through a gross anatomy course, female students tend to prioritize altruism more frequently in comparison to male students ( 32 ). Also, it has been demonstrated that female students are more supportive of commemoration ceremonies for body donors ( 33 ), which may, to some extent, account for the differences in responses. Another study found that female students are more likely to view the cadaver as a person than a specimen ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Pearson et al demonstrated that after frequent exposures to cadavers through a gross anatomy course, female students tend to prioritize altruism more frequently in comparison to male students ( 32 ). Also, it has been demonstrated that female students are more supportive of commemoration ceremonies for body donors ( 33 ), which may, to some extent, account for the differences in responses. Another study found that female students are more likely to view the cadaver as a person than a specimen ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…This enables the institution to express gratitude for the donation. It also provides a memorial for those donors who require a focal point for expressing their grief or observing traditional/cultural practices (El‐Haddad et al, 2021; Heathcote, 2014). Heathcote (2014), for example, reported on the usefulness of the online memorial, Nghia Trang, which allows Vietnamese women who have undergone an abortion a platform to consolidate their experience. Destruction and disposal: The various views surrounding the issue of keeping archival remains indefinitely or disposing them is subject to much debate.…”
Section: Where To From Here?mentioning
confidence: 99%
“…Organisation of the commemoration at MQU was preceded by several preparatory activities. From the published literature, it was recognized that the format of the ceremonies is dependent on several variables, including the resources and the way the anatomy teaching is organized at the particular institution as well as the local cultural milieu (McClea;Flack et al;Strkalj & Pather;da Rocha et al, 2020;El-Haddad et al).…”
Section: The Commemoration For Body Donorsmentioning
confidence: 99%
“…Because of the organisational complexity, the constraints of faculty organisation (anatomy at MQU is delivered from two different faculties) (Alexander et al, 2014;El-Haddad et al), and the fact that the human remains for anatomical teaching are sourced from other Australian universities (MQU does not have an embalming unit), it was decided that the commemoration would be introduced in a staged manner. To begin with, the commemorative ceremony was planned to be organised for students only, followed by a commemoration that would be inclusive to family members of the body donors.…”
Section: The Commemoration For Body Donorsmentioning
confidence: 99%
See 1 more Smart Citation